Odpowiedzi

2009-12-30T21:26:50+01:00
A) (x-2y)²+4(2x-3y)²=x²-4xy+4y²+4(4x²-12xy+9y²)=x²-4xy+4y²+16x²-48xy+36y²=17x²-52xy+40y²

b) (x+2)³-2(3x-1)³=x³+6x²+12x+8-2(27x³-27x²+9x-1)=x³+6x²+12x+8-54x³+54x²-18x+2=-53x³+60x²-6x+10
Najlepsza Odpowiedź!
2009-12-30T21:32:10+01:00
A) (x-2y)^2+4(2x-3y)^2= x²-4xy+4y²+4(4x²-12xy+9y²)=
=x²-4xy+4y²+16x²-48xy+36y²=17x²-52xy+40y²

(x+2)³-2(3x-1)³=x³+6x²+12x+8-2(27x³-27x²+9x-1)=
=x³+6x²+12x+8-54x³+54x²-18x+2=-53x³+60x²-6x+10

Skorzstałem ze wzorów skróconego mnożenia:
(x-y)²=x²-2xy+y²
(x+y)³=x³+3x²y+3xy²+y³
(x-y)³=x³-3x²y+3xy²-y³
2009-12-30T21:40:38+01:00
A) (x-2y)^2+4(2x-3y)^2= x^2 - 2*x*2y + 2y^2 + 4(2x^2 - 2*2x*3y + 3y^2
= x^2 - 4xy + 2y^2 + 8x^2 - 12xy + 3y^2 = 9x^2 - 16xy + 5y^2

b) (x+2)^3-2(3x-1)^3= x^3 + 3*a^2*2 + 3*x*2^2 + 2^3 - 2(3x^2 - 3*x^2*1 + 3x*1^2 - 1^3 = x^3 + 6x^2 + 12x + 8 - 6x^2 + 6x^2 - 6x - 1 =
x^3 + 6x^2 - 6x +7